Overtourism to Zero Tourism: Changing Tourists’ Perception of Crowding Post Covid-19 - Kainthola, Snigdha; Tiwari, Pinaz; R. Chowdhary, Nimit (Journal of Tourism, Sustainability and Well-being, 2021)
March 2020. The outbreak of the novel coronavirus restricted global mobility as cities and countries started to impose complete lockdown to curtail the spread of the deadly virus. The restricted movement of people and transport worldwide resulted in a metamorphosis from overtourism to zero tourism within a short period. This study aims to analyse the effect of COVID-19 on the tourists’ perceptions about crowding and how will this transition impact their decision while choosing a destination. In-depth interviews were conducted with tourists, and Nvivo12 plus was used to analyse the data. The study reveals that in the post-COVID-19 phase, tourists will be more sensitised towards crowding, and they would volunteer to avoid crowded places in the short run. Further, maintenance of social distancing norms and sanitised services at destinations will be a pre-requisite in selecting a destination. The study is a pioneer in analysing the changing tourist’s behaviour concerning crowding, evolving perceptions of overtourism for the tourists which will aid the stakeholders at the destinations in developing strategies. Inadvertently, the tourists visibly reflected the need for sustainable tourism.